https://journal.adre.ro/biomechanical-principles-success-criterion-in-implantology - Mușat Alexandru; Tibeica Andreea; Cretu Cosmin; Curca Razvan; Agop-Forna Doriana; Norina Forna (Romanian Dental Association for Education, 2023)
ABSTRACT The aim of this paper is to review current investigations on applications of the laws of biomechanics in implant therapy. Material and methods The literature was electronically searched. To identify the items needed for the study, we used books, various medical journals and dental education, in special the PubMed database and the keywords: occlusal considerations in implant therapy, principles of biomechanics in oral implantology, stress analysis, implant longevity. The inclusion criteria were as follows: English language, dental implants, in vitro studies, in vivo studies. Results From all publications only few dozen met the inclusion criteria. The studied aspects were: (1) pre-implantation analysis, (2) the application of the biomechanical principle, (3) maintaining the results. Conclusions Biomechanics is one of the most important consideration affecting design of the framework for an implant bone prosthesis. It must be analysed during diagnosis and treatment planning as it may influence the decision making process wich ultimately reflect on the longevity of implant supported prosthesis.